Mucinous carcinoma of the appendix: a case report - Aryadhana, Made Candra; Nangoy, Timmy Yonatan; Wijaya, I. Gusti Agung Brama; Darmawan, Made (International Journal of Advances in Medicine, 2024)
Mucinous carcinoma of the appendix is ​​​​a rare malignant tumor of the appendix. Incidence ranges about 0.01-0.2% in cases of malignancy in the gastrointestinal tract. Clinically, the symptoms appear to resemble acute appendicitis. The diagnosis was established at intraoperative time. Studies on this case are still few. A 69-year-old man complained of lower right abdominal pain since 6 days before going to Sanjiwani hospital. The patient also complained of fever, nausea, decreased appetite and constipation. Examination results temperature 37.6 0C, McBurney sign (+), rebound tenderness (+), localized defense on lower right abdomen. Ultrasound examination of the abdomen with an impression of the end tubular structure, a peristaltic diameter of 0.87 cm accompanied by a fluid collection, suspicious of appendicitis with perforation. Inflamed appendix and localized mucin were found at ileocaecal junction intraoperatively. The patient underwent a right hemicolectomy. Histopathological examination revealed a morphological picture suitable for mucinous carcinoma of the appendix. Mucinous carcinoma of the appendix is ​​​​a rare malignant tumor of appendix. Patients can have the same symptoms as appendicitis. Ultrasound investigations can find a picture like appendicitis. Mucinous carcinoma of the appendix is ​​more frequently found intraoperatively. Histopathological examination is necessary to determine a definitive diagnosis of mucinous carcinoma of the appendix. In high grade appendiceal mucinous neoplasm (HAMN) a right hemicolectomy can be performed and continued with adjuvant chemotherapy.